The influence of a balanced structure on the rotation effect of a build-up system. (February 2015) - Wei, Tieping; Yang, Xiaoxiang; Yao, Jinhui; Xu, Hang
Highlights: FEM modeling for the balanced structure of the build-up system is established. The relationship between Fm and the balanced structure's size was found. The factorial relative contribution for the rotation effect was obtained. Less Fm is helpful to improve the rotation effect of the build-up system. The critical limits of the H and t were determined using FEM simulations. Abstract: The influence of a balanced structure on the rotation effect of a build-up system was investigated using an orthogonal array, which can efficiently reduce the total number of experiments. Based on mechanical analysis, four primary influence factors of the balanced structure were specified, including the thickness, material and shape of the balanced platen, and the height of the bearing outer ring. Finite element method (FEM) was employed to investigate the relationship between four factors and the maximum differential of the horizontal side force ( Fm ) on a force transducer in the measurement of different orientations. We found that by decreasing the Fm, less rotation effect of the build-up system would be. The results of FEM simulations and the related assumption were validated by orthogonal-array experiments results. Furthermore, FEM simulations for the effects of the height of the bearing outer ring demonstrated that the magnitude of Fm initially decreases with increasing the height of the bearing outer ring, but then levels off.